Pengalaman Nurse Manager Menjalankan Strategi Pencegahan dan Pengendalian Infeksi Covid-19: Studi Fenomenologi - Herita Suasanta; Bustami Syam; Mula Tarigan (Jurnal Ners, 2025)
This study aims to explore the experience of nurse managers implementing strategies for preventing and controlling COVID-19 infection in hemodialysis units. The research uses qualitative methods with a descriptive phenomenological approach. Based on the results of the research analysis, 5 themes were found, namely: (1) Adapting to the COVID-19 PPI, (2) Managing the COVID-19 PPI, (3) Having obstacles in implementing the COVID-19 PPI, (4) Striving to increase the compliance of nurses, patients and visitors, (5) Have hopes for maximum implementation of PPI COVID-19. In conclusion, nurse managers, through leadership, preparedness and continuing to innovate, become a strategy for managing resources accompanied by motivation to form a solid nursing team in carrying out prevention and control of COVID-19 infections. Keywords: nurse manager, PPI Covid-19, hemodialysis unit